2015
DOI: 10.1590/0004-282x20150049
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up in sacroiliac joint pain patients treated with radiofrequency ablative therapy

Abstract: Sacroiliac joint (SIJ) pain is responsible for up to 40% of all cases of lumbar back pain.Objective Report the long-term efficacy of radiofrequency denervation for sacroiliac joint pain at six, twelve and eighteen months.Method Third-two adults’ patients with sacroiliac join pain diagnosis were included for a prospective study. Primary outcome measure was pain intensity on the Numeric Rating Scale (NRS). Secondary outcome measure was Patient Global Impression of Change Scale (PGIC).Results Short-term pain reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 20 publications
0
7
0
3
Order By: Relevance
“…Recently, Romero et al 31 reported short-term pain relief after RF denervation for sacroiliac joint pain with significant progressive decrease of NRS pain score determined at one and six months post-procedure, and long-term pain relief was sustained at 12…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Romero et al 31 reported short-term pain relief after RF denervation for sacroiliac joint pain with significant progressive decrease of NRS pain score determined at one and six months post-procedure, and long-term pain relief was sustained at 12…”
Section: Resultsmentioning
confidence: 99%
“…Monopolar conventional RFA was used in 6 of 16 observational studies . Two studies were prospective in design .…”
Section: Resultsmentioning
confidence: 99%
“…Monopolar conventional RFA was used in 6 of 16 observational studies. [13][14][15]21,39,40 Two studies were prospective in design. 21,39 Selection criteria for these studies varied, including either single or dual intra-articular SIJ injections, deep interosseous ligament injections with corticosteroid, or single intra-articular sacroiliac joint local anesthetic injection followed by one subsequent set of SLBBs including the L4 and L5 dorsal rami.…”
Section: Observational Studiesmentioning
confidence: 99%
“…Although all of these methods, pain relief is a challenger in many cases. 1,2,5 Previous study reported that pulsed radiofrequency denervation of the L4 and L5 primary dorsal rami and S1-3 lateral branches provide significant pain relief and functional improvement compared to intra-articular injection. 14 RF ablation in the sacroiliac joint is an action carried out based on the result of previous cadaver studies stating that there are anastomosed nerves with multiple dorsal primary branches around the neural foramen.…”
Section: Discussionmentioning
confidence: 99%
“…An average of 15-20% lower back pain originates from the sacroiliac joint. [1][2][3][4][5][6] This sacroiliac joint supports the unique curve-shaped diarthrodial joint, receiving innervation from the lumbosacral plexus. Neuro-physiologically, several studies have demonstrated that there are nociceptive and proprioceptive afferent nerves in the sacroiliac joint.…”
Section: Introductionmentioning
confidence: 94%